1988
DOI: 10.1007/bf00176838
|View full text |Cite
|
Sign up to set email alerts
|

Hangover hyperthermia in rats: relation to tolerance and external stimuli

Abstract: The recent finding of rebound hyperthermia in rats on the day after a single IP injection or oral intubation of ethanol was confirmed. In our studies, body temperature measured by rectal probe was significantly decreased for 8 h after 2.5 g/kg ethanol IP and was then significantly elevated 16-24 h after injection; increased vocalization during handling at 24 h was also found. However, rats isolated in a sound-attenuation chamber with remote temperature measurement showed no hyperthermia even though they were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Since animals in this study were given this habituation session 22 hr after their last injection, this motor suppression likely reflects withdrawal-induced hypomotility, which has been observed in rats up to 48 hr since their last EtOH administration (Macey et al, 1996). Decreases in motor activity join other measures, including convulsions, hypothermia, increased anxiety, hyperactivity, and rebound hyperthermia as being indicative of the withdrawal that occurs when chronic exposure to EtOH is terminated (Finn and Crabbe, 1997; Sinclair and Taira, 1988; Rasmussen et al, 2001; see Kliethermes, for review, 2005). There is ample evidence that adult rats show notable withdrawal after chronic EtOH exposure (File, 1991; 1993; 1994); however, withdrawal following chronic EtOH exposure during adolescence has been little investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Since animals in this study were given this habituation session 22 hr after their last injection, this motor suppression likely reflects withdrawal-induced hypomotility, which has been observed in rats up to 48 hr since their last EtOH administration (Macey et al, 1996). Decreases in motor activity join other measures, including convulsions, hypothermia, increased anxiety, hyperactivity, and rebound hyperthermia as being indicative of the withdrawal that occurs when chronic exposure to EtOH is terminated (Finn and Crabbe, 1997; Sinclair and Taira, 1988; Rasmussen et al, 2001; see Kliethermes, for review, 2005). There is ample evidence that adult rats show notable withdrawal after chronic EtOH exposure (File, 1991; 1993; 1994); however, withdrawal following chronic EtOH exposure during adolescence has been little investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few objective measures of alcohol withdrawal have been shown to be useful in detecting mild signs of alcohol withdrawal that occur after acute alcohol exposure in alcohol-naive rats (Gallaher and Egner, 1987;Holloway et al, 1993;Sinclair and Gustafsson, 1987;Sinclair and Taira, 1988). Our prior work in alcohol-naive rats demonstrated that acoustic startle reactivity to a tone stimulus is a reliable and quantifiable index of mild alcohol withdrawal that occurs after a single alcohol exposure in rats selectively bred for high or low alcohol intake (Chester et al, 2003).…”
mentioning
confidence: 99%
“…Mild withdrawal signs and symptoms are seen following acute alcohol exposure in both humans and animals, and, in humans, these signs are often referred to as "hangover" (Gallaher and Egner, 1987;Holloway et al, 1993;Swift and Davidson, 1998). There is no consensus in the rodent literature regarding the use of the terms "hangover" or "alcohol withdrawal" to describe the signs and symptoms that occur following acute alcohol exposure, and both terms have been used (Chester et al, 2002;Gallaher and Egner, 1987;Holloway et al, 1993;Metten et al, 1998;Sinclair and Taira, 1988). In our work, we have chosen to use the term "alco-hol withdrawal" to describe the behavioral and physiologic changes that occur following acute alcohol exposure at times when blood alcohol levels are falling and after blood alcohol levels have reached zero.…”
mentioning
confidence: 99%